Tyrosine phosphorylation related to thymic involution induced by diet restriction in comparison with aging - Izumi Takase (Journal of Advanced Biotechnology and Experimental Therapeutics, 2020)
Tyrosine phosphorylation signaling is known to be essential for the proliferation and differentiation of cells. Protein tyrosine kinases (PTKs) are present mainly in the lymphoid tissues including the thymus. The objective of the study was to investigate the expression of PTKs associated with stress-related thymic involution due to diet restriction compared with that due to aging. p56lck and p59fyn belong to the Src family membrane-associated PTKs. We found that diet-restricted rats had significantly lower thymus weights, and the expression of p59fyn was significantly decreased compared with the control group. In contrast, the expression of p56lck was not significantly different. We also found that aging-related thymic involution was not affected by the expression of those kinases. We confirmed that the mechanisms of diet-restricted thymic involution were different from those of aging-related thymic involution. It might be used as an index of chronic stress due to diet restriction in cases of child abuse or neglect. [ J Adv Biotechnol Exp Ther 2020; 3(3.000): 248-253]